O Programa Bolsa Família e o debate sobre direitos e democracia - Moraes, Isadora Coutinho (2017)
The entrance of Income Transfer Programs into the national public agenda has mobilized a large-scale debate on the potential of such policies to act as vectors for inclusion of the poor in the world of citizenship, as well as on the meaning and reach of such inclusion. The work goes into this debate after investigating the complaints and questions raised by participants in the Bolsa Família Program, residents of Nova Esperança, a small county in the Metropolitan Region of Maringá, Paraná, during meetings promoted by the Municipal Social Assistance. The record of the speeches - and of the silences - of the beneficiaries of Bolsa Família attending these meetings, as well as the opinions and reports given by the two municipal officials, who conducted the meetings, are taken as initial points to understand how beneficiaries of the program are related to the income coming from it and to the institutional discourse that surrounds it, thus reaching the dimensions of the relationship that this group creates with the State. For this purpose, the mentioned meetings were observed and open interviews were conducted with the psychologist and the social worker who acts as manager of Bolsa Família in the county, both responsible for organizing and conducting such meetings. Lastly, the work presents a discussion about the social meanings of the practice of consumption made possible by social policies, such as Income Transfer Programs, to its beneficiaries.